PELATIHAN SISTEM INFORMASI ADMINISTRASI KEUANGAN PADA KOPERASI WANITA MIFTAHUL JANNAH DI KABUPATEN TULUNGAGUNG - Maskur Maskur; Yosi Afandi; Nilawati Fiernaningsih; Pudji Herijanto; Yulis Nurul Aini (P3M Politeknik Negeri Malang, 2023)
Miftahul Jannah Women's Corporation in Tulungagung District, as a representative of micro-enterprises at the local level, faces various challenges in managing financial administration. Lack of knowledge of financial administration information systems is a major obstacle to improving the efficiency and transparency of co-operative financial management. Therefore, there is a need to train the financial administration information system to empower cooperatives and improve competitiveness. Training the financial management information system is a strategic solution to overcome the obstacles faced by the Miftahul Jannah Women's Corporation. Through a participatory approach, participants are involved in an understanding of the basic concepts of financial information technology, the use of financial software, and practical applications in a cooperative context. This approach is designed to accommodate a diverse level of digital literacy among participants. The training is designed with structured phases, including theory exposure, practical demonstration, and simulation training sessions. After the training, there was a significant improvement in the participants' ability to manage the co-operative financial administration. They are able to use financial software smoothly, compile accurate financial reports, and make better financial decisions. Positive impacts are also seen in increased transparency, accountability, and confidence among co-operative members. This training not only benefits the operational level of cooperatives but also empowers the economy of micro-enterprises in the region. With increased financial management capabilities, cooperatives can be more effective in managing resources, increasing production, and expanding market share. This empowerment contributes to local economic growth and improved welfare of co-operative members.